Layered P3-type K₀.₄Fe₀.₁Mn₀.₈Ti₀.₁O₂ as a low-cost and zero-strain electrode material for both potassium and sodium storage - Zhang, Xinyuan (2022)
Layered transition metal oxides are ideal Na+/K+ host materials due to their high theoretical capacities and appropriate working potentials, and the pursuit of cost-effective and environmentally friendly alternatives with high energy density and structural stability has remained a hot topic. Herein, we design and synthesize a low-cost and zero-strain cathode material, P3-type K0.4Fe0.1Mn0.8Ti0.1O2, which demonstrates superior properties for both potassium and sodium storage. The cathode delivers a reversible potassium storage capacity of 117 mA h g-1 at 20 mA g-1 and a fast rate capability of 71 mA h g-1 at 1000 mA g-1. In situ X-ray diffraction reveals a solid-solution transition with a negligible volume change of 0.5% upon K+ insertion/deinsertion that ensures long cycling stability over 300 cycles. When the material is employed for sodium storage, a spontaneous ion-exchange process with Na+-containing electrolytes occurs. Thanks to the positive effects of the remaining K+ ions that protect the layered structure from collapse as well as expand the interlayer structure, and the resulting K0.12Na0.28Fe0.1Mn0.8Ti0.1O2 demonstrates a high sodium storage capacity of 160 mA h g-1 and superior cycling stability with capacity retention of 81% after 300 cycles as well as fast kinetics.